Relationality and identity : understanding the existential meaning as a vocation to love - Risco Lázaro, Ana (2020)
This work investigates the fundamental contribution of interpersonal relationships in the configuration of personal identity, based on the consideration of the person as an essentially open and relational being, and of the body as a symbolic reality of the human vocation to love. Understanding that personal identity consists of the self-representation of oneself as a singular being and in homogeneity with others, and identifying through continuous changes and decisions as a being called to love, its achievement will require a gradual process that encompasses its entire existence. The identity stages through which it progresses - affiliation, nuptiality, paternity - require the acquisition of certain developmental capacities that provide the experience of welcoming and giving, essential elements of love. In the continuum of interpersonal relationships in which the person will be immersed in their own life journey from the first relationship with the one that gave birth to them, they will be able to develop their own self-awareness and advance in their development through the psychosocial skills that they will acquire to face the needs raised in each maturational stage until achieving the consolidation of their own personal identity in the authentically human experience of love as an existential meaning.